JRAA Vol.1 No.3, Nov 2014 BERBAGAI FAKTOR YANG DAPAT MEMPENGARUHI CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM LAPORAN TAHUNAN PERUSAHAAN: BERBAGAI FAKTOR YANG DAPAT MEMPENGARUHI CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM LAPORAN TAHUNAN PERUSAHAAN (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2014)
The study aimed to examine and analiyze relation independent board, management ownership , type of industry , the level of leverage , liquidity and profitability of a company with the level of CSR disclosure in annual reporting companies included in the LQ - 45 companies listed in Indonesia Stock Exchange The sample data used are companies LQ-45 index in the period February 2008 to January 2011 using the annual reports of each company for the financial year 2008 to 2010. Data were analyze using the classical assumption test and multiple linear regression analysis by the program SPSS ver 14 . The results of the study indicate that the variable independent board , management ownership , type of industry , the level of leverage , liquidity and profitability levels partially no significant effect on CSR disclosure in annual reports but simultaneously affect the CSR disclosure in annual reports with R Square 0, 225. It can be concluded that the companies included in the LQ - 45 had reveal more CSR information , detailed and transparent than other companies, that is why the six factors of independent variable in this study did not significantly affect CSR disclosure in annual reporting.